Differences in physiological characteristics between prepubescent female artistic and rhythmic gymnasts - Theos, A.; Dallas, G.; Kollias, L.; Papadopetraki, A.; Moustogiannis, A.; Grygorenko, O.; Maridaki, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Performance in gymnastics is the result of the optimal combination of muscle strength, speed and flexibility (Bassa et al., 2002). The purpose of the present study was to investigate differences in physiological characteristics between prepubescent female artistic and rhythmic gymnasts. Methods: Fourteen prepubescent female rhythmic gymnasts (RG) (age: 10.8 ± 1.0 yrs, body weight: 31.6 ± 4.1 kg, body height: 139.2 ± 7.4 cm) and eleven prepubescent female artistic gymnasts (AG) (age: 10.0 ± 1.4 yrs, body weight: 29.7 ± 5.2 kg, body height: 136.0 ± 9.1 cm) participated in this study. All subjects participated regularly ( 4 days/week) in sport specific training and had a training experience of 4.6 ± 1.5 yrs. Anthropometric characteristics as well as aerobic capacity (20m beep test), flexibility (sit and reach test), lower limbs strength and explosiveness (squat and countermovement jumps respectively), speed (20m sprint) and agility (agility T-Test) were measured. Differences between groups were analyzed using student`s t-test. Results are presented as mean ± SD. Results: There were no statistical differences between groups in age (p=0.16), body weight (p=0.31), body height (p=0.35), flexibility (RG=15.4 ± 3.8 vs. AG=16.2 ± 5.1 cm, p=0.65) and agility (RG=14.8 ± 1.1 vs. AG=14.9 ± 1.3 cm, p=0.81). Artistic gymnasts performed significantly better than rhythmic gymnasts in speed (RG=4.1 ± 0.2 vs. AG=3.8 ± 0.1 sec, p<0.01), lower limbs strength (RG=21.5 ± 3.0 vs. AG=26.4 ± 4.2 cm, p<0.01) and explosiveness (RG=26.1 ± 4.1 vs. AG=30.8 ± 5.5 cm, p<0.05), while rhythmic gymnasts performed better in aerobic capacity (RG=1234.3 ± 288.2 vs. AG=968.9 ± 172.4 m, p<0.05). Discussion: The results of the present study indicate that sport specific training in prepubescent female athletes seems to affect their physiological characteristics according to sports´ demands. Both sports demand stability and control of body movement, but since artistic gymnastics is characterized by short and explosive efforts (Mellos et al., 2014), artistic gymnasts seem to perform better in sprint and strength tests, while rhythmic gymnasts seem to be more aerobically trained.